Pentingnya Seorang Pemimpin dalam Mengelola Gereja dengan Baik - William Abraham Sitorus (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
Many leaders do not have good management which can cause a church to not grow well. This is a warning for church leaders to implement effective and efficient management so that the church and congregation can grow in God's perfection. The purpose of this study is to provide an understanding that management in a church is very necessary for the growth of the church in any aspect so that churches can open their minds to church management to support and develop church services. The author will use a qualitative research method, namely by applying an approach to literature studies. So guidance from God is needed so that leaders can manage the church according to God's plan. After that, the leader guides the congregation to join together and contribute to help realize the vision to be achieved in a church.